The role of bioenergy in transition to a sustainable bioeconomy: Study on EU countries - Ştefan Dragoş Cîrstea; Andreea Cîrstea; Irimie Emil Popa; Gabriel Radu (Amfiteatru Economic Journal, 2019)
Starting with the significant differences between the European Union member states regarding the implementation of the sustainable development goals stipulated by the United Nations and the transition from the fossil fuel economy to the one based on the principles of bio-economics, the article aims highlighting the correlation between the bioenergy production and a range of economic, environmental or innovation indicators for each Member State. The designed model uses data for 25 EU Member States collected for the period 2007-2013. The novelty of this study derives from the use of linear regression to estimate the impact of bioenergy evolution on the country's energy dependence and Panel Least Squares to identify the correlations between bioenergy and fossil fuel production, PIB per unit of energy use, the degree of innovation in the field and renewable energy generation. The obtained results show that the bioenergy-renewable-energy-dependency relationship is not significantly influenced by the economic crisis, even if the proposed model is weaker. At the same time, bioenergy positively correlates with the degree of innovation in the field or with the energy from natural gas and negatively with the economic efficiency of a state. The article presents the gap between countries regarding bioenergy, as well as their evolution during the analyzed period. All these values support the positive effects that bioenergy will have on the sustainable development of the bioeconomy. Bioenergy production can make a significant contribution to mitigating climate change while ensuring the diversification of energy resources in the long run.
Keywords: Q56; Q40; Q29; O10; C23; 330; bioenergy; bioeconomy; innovation; GDP per energy use; energy dependence; European Union